2022
DOI: 10.1155/2022/4671671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Methanol-Induced Optic Neuropathy: Correlation between Aetiology and Clinical Findings

Abstract: Purpose. To show the clinical characteristics, identify the magnetic resonance imaging (MRI) and optical coherence tomography (OCT) features, and observe the visual outcome of methanol-induced optic neuropathy. Methods. Clinical data were retrospectively collected from in-patients diagnosed with methanol-induced optic neuropathy in the Neuro-Ophthalmology Department of the Chinese People’s Liberation Army General Hospital from January 2016 to January 2021. Results. Eight patients were included in this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…[ 6 ] Additionally, a mitochondrial genetic defect as a predisposing factor has been suggested by Sun et al . [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Additionally, a mitochondrial genetic defect as a predisposing factor has been suggested by Sun et al . [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that magnetic resonance imaging abnormalities, like T1 enhancement and or long T2 in the retrobulbar segment of optic nerves, were found in methanol-induced optic neuropathy. Optical coherence tomography finding of ganglion cell layer loss, selectively involving the papillomacular bundle, was also reported [4]. Ma et al also mentioned that inhalational methanol toxicity may lead to serious damage to the optic nerve in a process of chronic intoxication with acute attack and poor prognosis [5].…”
Section: Introductionmentioning
confidence: 92%